An investigation of the mechanical properties of starch biofilms plasticized by glycerol - DEHANE, Aicha (Biopolymer Applications Journal, 2022)
Within the framework of sustainable growth, the use of biodegradable polymers as an alternative to synthetic polymers seems to be the best solution that could resolve waste disposal problems. The aim of this work was to prepare a biofilm based on a biodegradable polymer: starch plasticized by glycerol. Different rate of glycerol are added in order to plasticize the starch (15%, 20% and 30%). The method used for this preparation was casting, the structural and mechanical analysis was carried out to investigate the addition effect on of this plasticizer on the mechanical and structural properties.